2019
DOI: 10.3390/s19173655
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots—Assisted 2D Fluorescence for Pattern Based Sensing of Amino Acids, Oligopeptides and Neurotransmitters

Abstract: Quantum dots (QDs) are very attractive nanomaterials for analytical chemistry, due to high photostability, large surface area featuring numerous ways of bioconjugation with biomolecules, usually high quantum yield and long decay times. Their broad absorption spectra and narrow, sharp emission spectra of size-tunable fluorescence make them ideal tools for pattern-based sensing. However, almost always they are applied for specific sensing with zero-dimensional (0D) signal reporting (only peak heights or peak shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The presented work shows that application of excitation-emission fluorescence spectroscopy allows to capture subtle differences in the impact of neurotransmitters on fluorescent properties of QDs-GSH that are not visible when only changes in FL at one λ ex /λ em (zeroth-order data) or emission spectrum acquired at maximum λ ex (first-order data) are considered. It must be underlined that this is our another work [15] which shows that the use of excitation-emission fluorescence spectroscopy could possibly extend the sensing capability of QD patternbased systems developed in the future. Moreover, utilization of whole fluorescence profiles (EEM) of nanoreceptor may simplify the sensing element applied for the recognition of bioanalytes by providing analyte-specific multidimensional optical information.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The presented work shows that application of excitation-emission fluorescence spectroscopy allows to capture subtle differences in the impact of neurotransmitters on fluorescent properties of QDs-GSH that are not visible when only changes in FL at one λ ex /λ em (zeroth-order data) or emission spectrum acquired at maximum λ ex (first-order data) are considered. It must be underlined that this is our another work [15] which shows that the use of excitation-emission fluorescence spectroscopy could possibly extend the sensing capability of QD patternbased systems developed in the future. Moreover, utilization of whole fluorescence profiles (EEM) of nanoreceptor may simplify the sensing element applied for the recognition of bioanalytes by providing analyte-specific multidimensional optical information.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous work [15], we showed that the patternbased sensing with one type of QDs employing non-specific interactions can be achieved by using excitation-emission matrix (EEM) fluorescence spectroscopy, which is most commonly used in the 'fingerprint' analysis of foodstuff [16], environmental samples [17], and monitoring of biotechnological processes [18]. Although EEM spectroscopy was originally proposed as a technique allowing for complex characterization of samples containing many fluorophores [18], it has been shown that it can also be a useful tool for the characterization of nanomaterials [19,20], studying the interactions of QDs with biomolecules [21], as well as detection technique for QDs-based nanosensors [22,23].…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, specially designed nanomaterials may supply multidimensional optical information, which can be beneficial for the analysis’s overall time- and cost-effectiveness in chemical tongue approach [ 5 ]. The idea of capturing multidimensional optical information may be realized using advanced detection techniques such as excitation-emission matrix (EEM) fluorescence spectroscopy, covering the entire emission spectrum at multiple excitation wavelengths [ 6 ]. As we showed in our recent work, the resultant EEM spectrum encodes subtle differences in the impact of the studied neurotransmitters on the fluorescent properties of QDs, which in turn improves the efficiency of the analytes identification, compared to the traditional analysis based on single emission spectrum [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recognition of specific peptide sequences still poses a challenge. Our research group for the first time showed that QDs-assisted EEM fluorescence spectroscopy can be applied to recognize amino acids and several di- and tripeptides [ 6 ]. Then, we used a voltammetric chemical tongue to identify peptides within the group of Pro-Gly, carnosine, glutathione, Aβ 4-16 , and the α-factor N-terminus [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of second-order data combined with the appropriate chemometric model allows for the obtaining of the second-order advantage, which makes possible the determination of the target analyte, even in the presence of unknown and uncalibrated constituents of the sample matrix [ 16 ]. The data are classified as second-order or as a three-way array when a matrix per sample is obtained, such as the evolution of the PL spectrum throughout time (i.e., kinetic process of the interaction between QDs and analyte) [ 17 , 18 ] or when using an excitation–emission matrix (EEM) acquired via a rapid-scanning spectrofluorometer [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%